Correlative fractography: Combining scanning electron microscopy and light microscopes for qualitative and quantitative analysis of fracture surfaces - De Oliveira Hein, Luis Rogerio. [UNESP]; De Oliveira, José Alberto [UNESP]; De Campos, Kamila Amato [UNESP] (Oxford University Press (OUP), 2013)
Correlative fractography is a new expression proposed here to describe a new method for the association between scanning electron microscopy (SEM) and light microscopy (LM) for the qualitative and quantitative analysis of fracture surfaces. This article presents a new method involving the fusion of one elevation map obtained by extended depth from focus reconstruction from LM with exactly the same area by SEM and associated techniques, as X-ray mapping. The true topographic information is perfectly associated to local fracture mechanisms with this new technique, presented here as an alternative to stereo-pair reconstruction for the investigation of fractured components. The great advantage of this technique resides in the possibility of combining any imaging methods associated with LM and SEM for the same observed field from fracture surface. © Microscopy Society of America 2013.
Keywords: correlative microscopy; extended depth from focus reconstruction; image processing; light microscopy; quantitative fractography; scanning electron microscopy